2009
DOI: 10.1007/s11665-008-9251-3
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Characterization of HVOF Thermal Sprayed Functionally Graded Coatings Deposited onto a Lightweight Material

Abstract: There is a significant interest in lightweight materials (like aluminum, magnesium, titanium, and so on) containing a wear resistance coating, in such industries as the automotive industry, to replace heavy components with lighter parts in order to decrease vehicle weight and increase fuel efficiency. Functionally graded coatings, in which the composition, microstructure, and/or properties vary gradually from the bond coat to the top coat, may be applied to lightweight materials, not only to decrease weight, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The coatings quality can be controlled by the control of the particles in-flight temperature [98]. Moreover, in case of FGC it is suggested to control the powder with the lowest melting point in order to avoid excessive evaporation [99]. Prchlik et al [91] compared behavior of atmospheric plasma-sprayed Mo-Mo2C/stainless steel and HVOF-sprayed WC-Co/stainless steel functionally graded coatings.…”
Section: High Velocity Oxy-fuel and High Velocity Air-fuel Sprayingmentioning
confidence: 99%
See 1 more Smart Citation
“…The coatings quality can be controlled by the control of the particles in-flight temperature [98]. Moreover, in case of FGC it is suggested to control the powder with the lowest melting point in order to avoid excessive evaporation [99]. Prchlik et al [91] compared behavior of atmospheric plasma-sprayed Mo-Mo2C/stainless steel and HVOF-sprayed WC-Co/stainless steel functionally graded coatings.…”
Section: High Velocity Oxy-fuel and High Velocity Air-fuel Sprayingmentioning
confidence: 99%
“…The coatings quality can be controlled by the control of the particles in-flight temperature [98]. Moreover, in case of FGC it is suggested to control the powder with the lowest melting point in order to avoid excessive evaporation [99].…”
Section: High Velocity Oxy-fuel and High Velocity Air-fuel Sprayingmentioning
confidence: 99%
“…Therefore, it may directly or indirectly affect the oxide content and distribution, phase changes, and coating porosity. In addition, the very fast droplet solidification at cooling rates of about 10 6 -10 7 Ks −1 was found to be the reason for the formation of the amorphous phases [18] and the initiation of higher tensile residual stresses in the TWAS sprayed coatings [19][20][21]. Therefore, it is common that TWAS sprayed coatings require a post-treatment to achieve the required coating microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…This research will discuss the potential of using the HVOF technique to produce FGMs. Hence a functionally graded coating in which the composition, microstructure and properties vary gradually from the bond coat to the topcoat reported by Hasan et al (2009); Dussoubs et al (2001) resembles the graded coating of material R and S is shown in Figure 1 (b).…”
Section: Introductionmentioning
confidence: 99%